2014
DOI: 10.1039/c3cc48913b
|View full text |Cite
|
Sign up to set email alerts
|

Ni–Cu ion exchange observed for Ni(ii)–porphyrins on Cu(111)

Abstract: A Ni-Cu ion exchange has been observed for (5,15-dibromo-10,20-diphenylporphyrinato)nickel(II) (NiDBrDPP) and (5,10,15,20-tetrakis(4-bromophenyl)porphyrinato)nickel(II) (NiTBrPP) on Cu(111). The ion exchange proceeds at a faster rate for the NiDBrDPP/Cu(111) system compared to NiTBrPP/Cu(111). This is explained in terms of the macrocycle-substrate distance and the distortions that occur when the molecules are deposited on the Cu(111) surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 18 publications
3
39
0
Order By: Relevance
“…Therefore, a possible mechanism for multilayer metalation was shown to be the exchange of molecules between the first layer and the higher layers [714]. However, the findings by Chen et al could also be explained by an exchange of metal centers between the NiPc and the Cu(1 1 1) surface, as was proposed for another system [718] (cf. Section 6.5).…”
Section: Metalation Of Multilayers and At Bulk Interfacesmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, a possible mechanism for multilayer metalation was shown to be the exchange of molecules between the first layer and the higher layers [714]. However, the findings by Chen et al could also be explained by an exchange of metal centers between the NiPc and the Cu(1 1 1) surface, as was proposed for another system [718] (cf. Section 6.5).…”
Section: Metalation Of Multilayers and At Bulk Interfacesmentioning
confidence: 85%
“…Doyle et al reported that two Ni porphyrins with Br atoms in the periphery, NiDBrDPP and NiTBrPP, reacted with a Cu(1 1 1) surface by exchange of the Ni ion against a Cu ion [718]. This was concluded from a combined XPS and NEXAFS study: Monolayer Ni 2p 3/2 XP spectra showed how the peak related to the intact Ni porphyrin was increasingly replaced by a peak at a lower binding energy, which was attributed to Ni atoms on the Cu surface.…”
Section: Spontaneous and Forced Metal Exchange And Demetalationmentioning
confidence: 98%
“…The very low barrier that can be surmounted also at low temperature separates our approach from previous studies, in which Cu adatoms were used to replace cations in porphyrins. 25,26 The high annealing temperatures needed for these reactions are presumably due to the different starting configuration, in which the replacing metal centre starts from underneath the molecule, which is, as shown above, accompanied by a larger barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies describe the replacement of Ni and Co by Cu, which is supplied through the adatom gas on the Cu(111) surface in ultra-high vacuum. 25,26 A third study describes the exchange of Zn by Cu at the solid/ liquid interface. 27 No clear trends can be extracted from the existing literature: on the one hand Franke et al 27 report Zn substitution by Cu in a tetraphenylporphyrin network at the solid-liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of studies also exists addressing metalation of porphyrins on surfaces under ultrahigh vacuum with codeposited metal atoms, substrate metal atoms, oxide lattice ions, and recently also coordination of ions from aqueous solution . However, to our knowledge, the work of Doyle et al., showing the exchange of nickel metal centers with copper substrate atoms, is the only available study on metal center exchange of adsorbed porphyrins under ultrahigh vacuum.…”
Section: Introductionmentioning
confidence: 99%